2008
DOI: 10.1128/aem.01014-07
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Microbial Utilization of Petroleum Hydrocarbons in Salt Marsh Sediments by Using the 13 C Content of Bacterial rRNA

Abstract: Natural remediation of oil spills is catalyzed by complex microbial consortia. Here we took a wholecommunity approach to investigate bacterial incorporation of petroleum hydrocarbons from a simulated oil spill. We utilized the natural difference in carbon isotopic abundance between a salt marsh ecosystem supported by the 13 C-enriched C 4 grass Spartina alterniflora and 13 C-depleted petroleum to monitor changes in the 13 C content of biomass. Magnetic bead capture methods for selective recovery of bacterial R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 74 publications
(105 reference statements)
2
28
0
Order By: Relevance
“…This detection limit was an order of magnitude lower than in previous Mag-SIP studies that used traditional EA-IRMS (25,26). Similar sensitivities were obtained by Pearson et al (37), who used a spooling-wire interface to determine natural stable isotope ratios in total bacterial 16S rRNA. These improvements enabled us for the first time to apply Mag-SIP at family level resolution, and we demonstrated the method in an experiment on substrate utilization by sulfate-reducing Deltaproteobacteria in anoxic marine sediment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This detection limit was an order of magnitude lower than in previous Mag-SIP studies that used traditional EA-IRMS (25,26). Similar sensitivities were obtained by Pearson et al (37), who used a spooling-wire interface to determine natural stable isotope ratios in total bacterial 16S rRNA. These improvements enabled us for the first time to apply Mag-SIP at family level resolution, and we demonstrated the method in an experiment on substrate utilization by sulfate-reducing Deltaproteobacteria in anoxic marine sediment.…”
Section: Discussionsupporting
confidence: 74%
“…The main advantage of Mag-SIP over other nucleic acid-based SIP methods is that in principle much lower labeling levels can be applied (about 0.001% versus Ͼ10% 13 C, respectively), as label detection is based on IRMS methods. For instance, it has been shown that the method can be used to study the effects of oil pollution on natural ␦ 13 C ratios of bacterial communities in sediments (37). Moreover, Mag-SIP is not based on PCR, as the isotope ratio of the target rRNA is directly measured without amplification of nucleic acid, avoiding possible PCR artifacts.…”
mentioning
confidence: 99%
“…However, we did observe significant negative correlations at the basin station between cell-specific leucine incorporation by HNA cells and abundances of Gammaproteobacteria and Cytophaga-like cells. Recent methodological developments (Orphan et al 2002, Pearson et al 2008 may provide the potential to quantify metabolic activity of targeted phylogenetic groups in future studies. The activity of aquatic bacterioplankton exists on a continuum (Smith & del Giorgio 2003), thus there is no reason to think that bacterial activity will be constant across any one phylogenetic group.…”
Section: Discussionmentioning
confidence: 99%
“…Strain MesG1.Ag.4.2 belongs to a lineage previously identified only through 16S rRNA gene sequences culled from samples taken from low temperature environments (Briones et al 2007;Chouari et al 2005;Dollhopf et al 2001;Enright et al 2007;Fernandez et al 2008;Holoman et al 1998;Leven et al 2007;Pearson et al 2008;Pham et al 2009;Rowe et al 2008;Watts et al 2001;Wu et al 2000;Yan et al 2006;Yoshida et al 2005;Zhao et al 2008). Consequently, these phylotypes were called mesotogas to reflect their likely mesophilic growth temperatures (Nesbø et al 2006(Nesbø et al , 2010.…”
Section: Introductionmentioning
confidence: 99%